An empirical analysis of analysts’ cash flow forecasts - DeFond, Mark L.; Hung, Mingyi (Journal of Accounting and Economics, 2003)
This study investigates the recent trend in analysts disseminating operating cash flow forecasts. We find that analysts tend to forecast cash flows for firms where accounting, operating and financing characteristics suggest that cash flows are useful in interpreting earnings and assessing firm viability. Specifically, we find that analysts tend to forecast cash flows for firms with (1) large accruals, (2) more heterogeneous accounting choices relative to their industry peers, (3) high earnings volatility, (4) high capital intensity, and (5) poor financial health. These findings are consistent with financial analysts responding to market-based incentives to provide market participants with value-relevant information.